Structural bioinformatics and gene expression analysis of maturase K from Lavandula angustifolia (lavender) - Liu, Dafeng; Li, Na; Song, Daoqi; Lv, Zhenming (Frontiers in Molecular Biosciences, 2025)
The chloroplast genome of plants contains a single gene encoding the splicing factor Maturase K (MatK). To elucidate the functional role and underlying mechanism of MatK, we investigated it in Lavandula angustifolia (lavender). Structural models of MatK1 and Matk2 were predicted using AlphaFold2, and potential active site residues were identified via the GalaxyWEB program. The results of RT-qPCR analysis revealed that the expression of MatK1 and MatK2 peaked in leaves at 14:00. For heat treatments, MatK1 expression in leaves increased with the duration of heat exposure, reaching its highest levels at 40°C for 3 h and 30°C for 6 h, before declining. Similarly, under salt treatment, MatK1 expression in leaves showed an increasing trend with exposure time, peaking at 300 mM NaCl for 3 h and 200 mM for 12 h, before decreasing. This study provides the first detailed characterization of Maturase K in L. angustifolia.